Strategi Kepala Madrasah Untuk Mengembangkan Kompetensi Guru Di MA. Mambaul Hikmah Rubaru Sumenep Madura - Achmad Fauzan; Zakariyah Zakariyah; Ashari Ashari (CV. ITTC INDONESIA, 2025)
The research results show that: 1). There are various strategies for school principals to develop teacher competence in MA. Mambaul Hikmah Rubaru Sumenep Madura, in order to develop teacher competence to be able to realize the vision and mission of the institution, among the strategies that have been carried out are as follows; Motivating teachers to create and innovate, Holding workshops or workshops, Delegating Teachers to Participate in Education Training and Seminars, Motivating Teachers to Make Scientific Papers, Holding Comparative Study Programs, Giving Awards, Implementing Discipline of Teachers, Employees, and Students, Conducting Educational Supervision, Madrasas (Stake Holder) Through exemplary, Improving the Quality of Facilities and Infrastructure, providing opportunities for advanced stages. 2). The driving and inhibiting factors faced by madrasah heads in developing teacher competence in MA. Mambaul Hikmah Rubaru Sumenep Madura, among others; driving factor; encouragement and support from the head, factors from teachers, facilities and infrastructure factors, students or students. Inhibiting factors; Lack of motivation from within the teacher himself, The economy is not yet stable and still low, Lack of motivation or encouragement from parents.